2019
DOI: 10.5334/aogh.2327
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Pediatric Emergency Room Utilization in an Urban Community Hospital in Santiago, Dominican Republic

Abstract: Background: In low resource settings, maximizing effective use of emergency room (ER) services is imperative. This problem is anecdotally observed in the public hospital setting in Santiago, Dominican Republic (DR). There are no studies presently published examining ER use in this pediatric population or reasons caregivers choose to utilize the pediatric ER. Financial and systemic limitations have been previously cited as important contributors to the high pediatric mortality rate in the DR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Patient education materials certainly cannot prevent application issues on the provider/ortho tech's end; however, these educational materials can and should be inclusive of signs and symptoms of underlying skin issues such as pressure ulcers and be emphatic about contacting the clinic immediately upon the caregiver's suspicion of such. It is prudent to consider parental/caregiver perceptions when providing any education; ED visits, RTC, treatment compliance, and trust in providers have all been attributed to the perceived urgency of illness by the caretaker (Lockwood et al, 2019; Sofu et al, 2015). Our website did advise caregivers to contact the clinic if their child were to experience an area of pain/burning inside the cast, as this is a symptom of potential pressure ulcer; however, all of the skin issues in the postintervention group were reported or discovered at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education materials certainly cannot prevent application issues on the provider/ortho tech's end; however, these educational materials can and should be inclusive of signs and symptoms of underlying skin issues such as pressure ulcers and be emphatic about contacting the clinic immediately upon the caregiver's suspicion of such. It is prudent to consider parental/caregiver perceptions when providing any education; ED visits, RTC, treatment compliance, and trust in providers have all been attributed to the perceived urgency of illness by the caretaker (Lockwood et al, 2019; Sofu et al, 2015). Our website did advise caregivers to contact the clinic if their child were to experience an area of pain/burning inside the cast, as this is a symptom of potential pressure ulcer; however, all of the skin issues in the postintervention group were reported or discovered at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16] This data reiterates that the notion of urgency of parents and guardians is different from the real complexity of the symptomatology. 7 The search for emergency services by most parents because of fever -one of the most common symptoms in childhoodserves as a parameter to determine the severity of the child's illness. Thus, fever becomes the main symptom for which parents seek emergency services, even in unnecessary cases.…”
Section: Discussionmentioning
confidence: 99%
“…The high demand of children for pediatric emergency services interferes with the quality of care; patients who really need agility in care wait for hours with those who demand primary care and orientation. 6 A study 7 showed that the perception of the children's caregivers does not match the real need for emergency care services, when 72% of the caregivers identified the problem that brought them to the unit as extremely urgent; however, 82% of the children were later classified as non-urgent. This discrepancy may, according to the study, be related to the caregivers' low educational level.…”
Section: Introductionmentioning
confidence: 99%